Polk family papers
Two volumes (circa 200 items) containing correspondence, indentures and legal agreements, circulars, pamphlets, and other papers. Consists chiefly of letters to William Polk concerning the University of North Carolina, elections of 1824 and 1828, Bank of the United States, and the politics of John Quincy Adams, William Harris Crawford, and Henry Clay, and Andrew Jackson. Includes copies of documents relating to the Mecklenburg Declaration of Independence and a biography (1859) of William Polk. Polk family members represented include Leonidas Polk and James K. Polk. Correspondents include John Quincy Adams, Alfred Balch, John Branch, Joseph Caldwell, Andrew Jackson Donelson, John Henry Eaton, Daniel Graham, Andrew Jackson, William Berkeley Lewis, Willie Person Mangum, and Thomas Ruffin.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Family of North Carolina. Family members represented include James K. Polk, Leonidas Polk, and William Polk.
Collection material in English.
Keywords: Adams, John Quincy, -- 1767-1848.; Adams, John Quincy, -- 1767-1848 -- Correspondence; Balch, Alfred -- Correspondence; Branch, John, -- 1782-1863 -- Correspondence; Caldwell, Joseph, -- 1773-1835 -- Correspondence; Clay, Henry, -- 1777-1852.; Crawford, William Harris, -- 1772-1834.; Donelson, Andrew Jackson, -- 1799-1871 -- Correspondence; Eaton, John Henry, -- 1790-1856 -- Correspondence; Graham, Daniel, -- 1789-1869 -- Correspondence; Jackson, Andrew, -- 1767-1845.; Jackson, Andrew, -- 1767-1845 -- Correspondence; Lewis, William Berkeley, -- 1784-1866 -- Correspondence; Mangum, Willie Person, -- 1792-1861 -- Correspondence; Polk, James K. -- 1795-1849.; Polk, Leonidas, -- 1806-1864.; Polk, William, -- 1758-1834.; Polk, William, -- 1758-1834 -- Correspondence; Ruffin, Thomas, -- 1787-1870 -- Correspondence; Polk family; Bank of the United States (1816-1836); University of North Carolina at Chapel Hill -- History; Mecklenburg Declaration of Independence; Elections -- United States -- 1824.; Elections -- United States -- 1828.; Presidents -- United States -- Election -- 1824.; Presidents -- United States -- Election -- 1828.; Universities and colleges -- North Carolina; North Carolina -- Social life and customs